Herpes Simplex Virus Entry by a Nonconventional Endocytic Pathway - Tebaldi, Giulia (J Virol, 2020)
Herpes simplex virus 1 (HSV-1) causes significant morbidity and mortality in humans worldwide. HSV-1 enters epithelial cells via an endocytosis mechanism that is low-pH dependent. However, the precise intracellular pathway has not been identified, including the compartment where fusion occurs. In this study, we utilized a combination of molecular and pharmacological approaches to better characterize HSV entry by endocytosis. HSV-1 entry was unaltered in both cells treated with small interfering RNA (siRNA) to Rab5 or Rab7 and cells expressing dominant negative forms of these GTPases, suggesting entry is independent of the conventional endo-lysosomal network. The fungal metabolite brefeldin A (BFA) and the quinoline compound Golgicide A (GCA) inhibited HSV-1 entry via beta-galactosidase reporter assay and impaired incoming virus transport to the nuclear periphery, suggesting a role for trans-Golgi network (TGN) functions and retrograde transport in HSV entry. Silencing of Rab9 or Rab11 GTPases, which are involved in the retrograde transport pathway, resulted in only a slight reduction in HSV infection. Together, these results suggest that HSV enters host cells by an intracellular route independent of the lysosome-terminal endocytic pathway. IMPORTANCE Herpes simplex virus 1 (HSV-1), the prototype alphaherpesvirus, is ubiquitous in the human population and causes lifelong infection that can be fatal in neonatal and immunocompromised individuals. HSV enters many cell types by endocytosis, including epithelial cells, the site of primary infection in the host. The intracellular itinerary for HSV entry remains unclear. We probed the potential involvement of several Rab GTPases in HSV-1 entry and suggest that endocytic entry of HSV-1 is independent of the canonical lysosome-terminal pathway. A nontraditional endocytic route may be employed, such as one that intersects with the trans-Golgi network (TGN). These results may lead to novel targets for intervention.